Analisis Ekonomi Wilayah Kabupaten Eks-Karesidenan Surakarta (Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen Dan Klaten) Tahun 2010-2014 - Prihatini, Setiyo; , Drs. M. Musiyam, M.TP; , Dra. Umrotun, M.Si (2017)
The purpose of this research is to know the contribution of the economic sector in each district of Surakarta Residency Year ex-2010-2014 and analyze the sector's flagship on each ex-Resident of Surakarta Regency Years 2010-2014. This study uses secondary data published by the Central Bureau of statistics (BPS) and ex-Resident of Surakarta Regency in 2010-2014. Analytical tools used in this study i.e. the Share Shiftanalysis and Location Question (LQ). The rank of the first sector of the processing industry in Boyolali Regency, Sukoharjo Regency, Karanganyar Regency, Sragen Regency and Klaten Regency, while the sectors of electricity, gas and clean water, the second ranking Boyolali district and regional economic sector Karanganyar Regency is the agricultural sector, while the Sukoharjo Regency, Wonogiri Regency, Sragen Regency, and Klaten Regency is a sector of trade, hotels and restaurants, ranking third and Boyolali district in the Karanganyar Regency economic sector is a sector trade area, hotels and restaurants, while the Sukoharjo, Klaten, Sragen district and is the agricultural sector, in contrast to the economic sector area of Karanganyar Regency is a sector of trade, hotels and restaurants, ranking fourth regional economic sector and Boyolali district in Karanganyar Regency, and Wonogiri Regency is sector services, Sukoharjo Regency is the sector of the transportand communcations, while the building sector is Sragen. The results of calculation of the index Location Question (LQ berdasrakan GRP ex-Resident of Surakarta Regency years 2010-2014 i.e. Boyolali district there are four flagship sectors i.e. sectors of mining and excavation, services sector, the agricultural sector, and the building sector, Sukoharjo Regency there were six flagship sectors i.e. sectors of the processing industry, the transport and communications sector, financial sector, rentals and service companies, trade, hotels and restaurants, building sector, and sector services Karanganyar Regency, there were three winning sectors i.e. sectors of electricity, gas and water supply sector, the processing industry and services sectors, there are four flagship sectors, namely agriculture, services sector, the mining sector and the transport sector, and the excavation and communications, Sragen district there are four flagship sectors i.e. sectors of trade, hotels and restaurants, services sector, building sector and mining sector and the excavation, and Klaten there are six flagship sectors i.e. sectors services the mining sector, and excavation, trade, hotels and restaurants, industrial processing sector, the sector of building and transport and communications sectors. Keywords: Economic Region, contribute, ex-Resident of Surakarta, the leading Sector, Location Analysis Question (LQ), Shift and Share